The effect of human resources practice on job satisfaction among the academics staffs of Yarmok University in Jordan - Almomani, Ashraf Ali Ahmad (2016)
The main purpose of this study is to examine the effect of human resources practice on job satisfaction among the academics staffs of Yarmok University in Jordan. The factors that examined in this study are training and development, compensations, performance appraisal, benefit as well as safety and health. The Yarmok Universitie academics staffs were the respondent of this study. The respondent was obtained from the human resource department of the University, a total of 283 questionnaires were distributed to obtained the primary data used for this study, both descriptive and internal analysis employed in this study, the result shows that training and development, compensation, performance appraisal, safety and health precedents employee job satisfaction with training and development showing strongest contribution, suggestions are made for future research on ways to enhance job satisfaction among employees